LANSKAP POLITIK LOKAL JAWA PESISIRAN PADA GURIT KARYA ATMO TAN SIDIK: KAJIAN SEMIOTIKA - Dinda, Dinda Fitri Nurul Pramesti; Sucipto Hadi Purnomo (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
Literature works often reflect the daily lives of people, including the dynamics of local politics. Literature, especially poetry, serves as a medium for writers to express aspirations and concern representing public unrest toward ongoing political conditions. The anthology geguritan Dugale Asu Maring Menungsa is one such literature work that successfully reveals the portrayal of local political landscape represented in the guritan works of Atmo Tan Sidik. This research is qualitative descriptive in nature, using Roland Barthes semiotic approach which consists of three types of coding: denotation, connotation, and myth. The study employs note-taking techniques to collect and map data. Data analysis using the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and verification. The findings show that local political practices in Tegal, Central Java have experienced a distortion of values. The poetry shows that elections have lost their spirit of struggle and have turned into a spectacle of entertainment and material transaction.